Weighing performances of a novel EMFC weighing cell with axis- symmetric structure - Yoon, Kyung Taek; Kim, Dongmin; Lee, Moon Gu; Choi, Young Man (European Society for Precision Engineering and Nanotechnology, Conference Proceedings - 22nd International Conference and Exhibition, EUSPEN 2022, 2022)
In our previous work, a novel electromagnetic force compensation weighing cell was proposed. The proposed weighing cell was developed as a unique force comparator for measuring difference between gravitational force and electromagnetic force in the KRISS Kibble balance. The proposed weighing cell is designed axial-symmetrically, unlike conventional precision weighing cells, with respect to the center of gravity axis using triple compound guide mechanisms and a tri-lever mechanism. The weighing cell employs three independent mass measurement units to measure the test mass by dividing it, improving weighing accuracy and structural stability. Moreover, it gives tilt information which enables correct alignment to the gravity axis. The repeatability of the weighing cell was 0.7 mg with respect to 1 kg test mass and improved to up to 0.2 mg when the zero-point drift was compensated in the air. Lastly, experimental result of ground-tilt response of the weighing cell suggested that a tilt angle can be estimated by observing the change in the compensating force of each mass measurement unit.
Keywords: Cell-be; Cell/B.E; Cell/BE; Electromagnetic force compensations; Force; Force comparator; Mass measurements; Measuring instruments; Performance; Symmetric structures; Force; Measuring instrument; Mechatronic; Metrology